A Survey of Commonly Used Cryptographic Algorithms in Information Security (International Journal of Engineering and Computer Science, 2015)
Progression in computing powers and parallelism technology are creating obstruction for credible security especially in electronic information transactions under cryptosystems. An enormous set of cryptographic schemes persist in which each has its own affirmative and feeble characteristics. Some schemes carry the use of long bits key and some support the use of small key. Practical cryptosystems are either symmetric or asymmetric in nature. With the fast progression of digital data exchange in electronic way, information security is becoming much more important in data storage and transmission.   Network Security is the most vital component in information security because it is responsible for securing all information passed through networked computers. Cryptography is the one of the main categories of computer security that converts information from its normal form into an unreadable form by using Encryption and Decryption Techniques. This survey compares trendy encryption techniques for convinced selection of both key and cryptographic scheme.